1975
DOI: 10.1007/bf00579943
|View full text |Cite
|
Sign up to set email alerts
|

3H-Inulin and electrolyte concentrations in Bowman's capsule in rat kidney

Abstract: Micropuncture experiments were performed on Bowman's capsules in male and female non-diuretic Munich rats. 55 samples were collected and analysed for Na, Cl, K, Ca, P, Mg and 3H-inulin contents. Their electrolyte concentrations were compared to the corresponding concentrations obtained from plasma artificial ultrafiltrates. Compared to normal Wistar rats, our Munich rats had several special characteristics: high arterial pressure (115-155 mm Hg), high concentrating ability (phi equals 2684 mOsm/1) and high NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…This correction factor is in close agreement with that found by Strickler et al (7). Moreover, Le Grimellec et al (19) found that the phosphate concentration in fluid collected from Bowman's capsule of rats agrees closely with that found in ultrafiltrates of whole plasma through Cuprophan membranes (Enka AG., Plant Wuppertal-Bjarmen Wuppertal 2 West Germany). In the text and figures, plasma 32P04 refers to UF 32po4, i.e.…”
Section: Methodssupporting
confidence: 56%
“…This correction factor is in close agreement with that found by Strickler et al (7). Moreover, Le Grimellec et al (19) found that the phosphate concentration in fluid collected from Bowman's capsule of rats agrees closely with that found in ultrafiltrates of whole plasma through Cuprophan membranes (Enka AG., Plant Wuppertal-Bjarmen Wuppertal 2 West Germany). In the text and figures, plasma 32P04 refers to UF 32po4, i.e.…”
Section: Methodssupporting
confidence: 56%
“…Parathyroidectomy (32, 33) and phosphate loading (31-33) appear to have no discernible effect on the ultrafilterable fraction of phosphate as determined in in vitro systems. Moreover, LeGrimellec et al (34) have shown that the filterability of phosphate across the glomerular filtration barrier is essentially identical to the value measured across cuprophane. Thus, it appears that the maximum increment in filtered load which could be attributed to a change in phosphate ultrafilterability must be less than 10%.…”
Section: Resultsmentioning
confidence: 74%
“…Increased fractional excretion ofphosphate in mutants (47.2 +4 vs. 30.8+2% in controls) was associated with reduced fractional and absolute reabsorption in the proximal convoluted tubule and more distal sites. Acute thyroparathyroidectomy (TPTX) increased phosphate reabsorption in both mutants and controls with a fall in fractional phosphate excretion to _7.5% in both groups indicating that PTH modified the degree of phosphaturia in the intact mutants.…”
mentioning
confidence: 87%